Radiation Induced Enhancement of Hydrogen Influence on Luminescent Properties of nc-Si/SiO(2) Structures - Lisovskyy, Igor (Nanoscale Res Lett, 2016)
Using photo-luminescence, infrared spectroscopy, and electron spin resonance technique, the silicon dioxide films with embedded silicon nanocrystals (nc-Si/SiO(2) structures) have been investigated after γ-irradiation with the dose 2 × 10(7) rad and subsequent annealing at 450 °C in hydrogen ambient. For the first time, it was shown that such a radiation-thermal treatment results in significant increase of the luminescence intensity, in a red shift of the photoluminescence spectra, and in disappearance of the electron-spin resonance signal related to silicon broken bonds. This effect has been explained by passivation of silicon broken bonds at the nc-Si–SiO(2) interface with hydrogen and by generation of new luminescence centers, these centers being created at elevated temperatures due to transformation of radiation-induced defects.